2015
DOI: 10.1002/anie.201506933
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Dual Catalytic α‐Allylation of Protected α‐Amino‐ and α‐Hydroxyacetaldehydes

Abstract: Fully stereodivergent dual-catalytic α-allylation of protected α-amino- and α-hydroxyacetaldehydes is achieved through iridium- and amine-catalyzed substitution of racemic allylic alcohols with chiral enamines generated in situ. The operationally simple method furnishes useful aldehyde building blocks in good yields, more than 99% ee, and with d.r. values greater than 20:1 in some cases. Additionally, the γ,δ-unsaturated products can be further functionalized in a stereodivergent fashion with high selectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(58 citation statements)
references
References 96 publications
1
56
0
Order By: Relevance
“…Recently, Carreira and co-workers reported the allylation of aldehydes in a stereodivergent fashion by the synergistic reactivity of iridium and amine catalysts under acidic conditions. 3 Zhang and co-workers reported the combination of iridium and zinc catalysts for the related allylation of α -hydroxy phenones. 4 An approach to the stereodivergent allylation of carbonyl compounds in the carboxylic acid oxidation state has not been published.…”
mentioning
confidence: 99%
“…Recently, Carreira and co-workers reported the allylation of aldehydes in a stereodivergent fashion by the synergistic reactivity of iridium and amine catalysts under acidic conditions. 3 Zhang and co-workers reported the combination of iridium and zinc catalysts for the related allylation of α -hydroxy phenones. 4 An approach to the stereodivergent allylation of carbonyl compounds in the carboxylic acid oxidation state has not been published.…”
mentioning
confidence: 99%
“…In a follow-up study, the authors reported that this method tolerates α -heteroatoms ( 47 , R = NPhth or OBn) in similarly high yields and selectivities, though trichloroacetic acid is required as the cocatalyst. 19 …”
Section: Dual Catalyst-controlled Processesmentioning
confidence: 99%
“…58 We found that the use of proton sponge in place of LiO t -Bu afforded the desired branched product 6 with high regioselectivity (93:7, 6 : 7 ) and diastereoselectivity (7.9:1 dr), though in a modest 66% enantiomeric excess (entry 6). A brief study of ligand frameworks (entries 7–9) 9 revealed 3,3’-diphenyl-phosphoramidite L2 to be optimal.…”
mentioning
confidence: 92%